Utilization of the Chronic Disease Management Program (Prolanis) at Suak Ribee Primary Health Center, Indonesia - Osaria Darmayanti; Darmawan Darmawan; Eva Flourentina Kusumawardani; Safrizal Safrizal; Siti Maisyaroh Fitri Siregar (PT.Mantaya Idea Batara, 2025)
Background: The Prolanis Program at the Suak Ribee Health Center includes monthly health education, biannual supporting examinations, pharmaceutical services (DRR), group exercise sessions, and home visit activities. This study aimed to identify the determinants influencing the utilization of the BPJS Health Prolanis program at the Suak Ribee Health Center.Method: The research was conducted from January 7 to February 7, 2025, involving 66 randomly selected participants using a quantitative cross-sectional design. Data were analyzed through univariate and bivariate analyses using the chi-square test, and multivariate analysis using logistic regression..Result: The results revealed that age (p = 0.048), gender (p = 0.003, OR = 6.167), knowledge (p = 0.042, OR = 3.630), the role of health workers (p = 0.015, OR = 4.750), and family support (p = 0.045, OR = 3.600) were significantly associated with the utilization of Prolanis. Education level, however, showed no significant effect (p = 0.374, OR = 1.875). Gender emerged as the most dominant factor (p = 0.002, OR = 8.930).Conclusion: n conclusion, age, gender, knowledge, the role of health workers, and family support influence the utilization of the Prolanis program, whereas education does not. It is recommended that the Suak Ribee Health Center increase male participation in Prolanis, for example by organizing exercise sessions on weekends or in the afternoon, and by conducting home visits as a separate program to better target less active participants